Direct phosphonation of quinoxalin-2(1H)-ones under transition-metal-free conditions. Issue 13 (18th January 2016) - Gao, Ming; Li, Yi; Xie, Lijuan; Chauvin, Remi; Cui, Xiuling
Abstract : A direct C–H bond phosphonation of quinoxalin-2(1 H )-ones with H-phosphonates, H-phosphinates or H-phosphine oxides has been developed. Abstract : A direct C–H bond phosphonation of quinoxalin-2(1 H )-ones with H-phosphonates, H-phosphinates or H-phosphine oxides has been developed. A wide variety of heteroaryl phosphonates were obtained in up to 92% yield for 20 examples under transition-metal-free conditions. This protocol tolerates a broad scope of substrates and features practicality, high efficiency, environmental friendliness and atom economy.